Molecular genetic characterization of Ongole and Deoni cattle using microsatellite markers* - Srinivas, Sriramula; Rao, G Narasimha; Ahmed, Niyaz; Gupta, Ramesh (The Indian Journal of Animal Sciences, 2011)
The study presents the genetic structure of the 2 zebu breed populations, Ongle and Deoni, which were characterized using 11 microsatellite markers. All the markers were polymorphic in both the breeds. The mean number of allele per locus was 5.91. The PIC values ranged from 1.140 to 0.682 in Ongle and 0.222 to 0.792 in Deoni. The observed heterozygosity in Ollgole across the loci was 0.555 while it was 0.628 in DeonL The overall genetic divergence between 2 breeds, PST was 0.090, indicating moderate genetic relationship.